Study of the Effect of Reduced Iron Temperature Rising on Total Carbon Formation in Iron Reactor Isobaric and Cooling Zone. (21st February 2010) - Alamsari, Bayu; Torii, Shuichi; Trianto, Azis; Bindar, Yazid
Abstract : We presented the mathematical model in the iron reactor. The model was limited to Isobaric Zone and Cooling Zone termed as IZ and CZ, respectively. The simulation was done by adapting the heat and mass transfer equations. The main purpose of this paper is to estimate the temperature increasing effect of reduced-iron on sponge-iron quality. The calculations are solved using Finite Element Method (FEM). The results showed that the temperature and concentration values from the simulation have high similarity to the reference data with Root-Mean-Square Error (RMSE) about 0.7. The formation of total-carbon in the both zones decreased metallization degree until 1.72%. The increase in reduced-iron temperature higher than 1200 K produces total-carbon higher than 3%. Thus the increase in reduced-iron temperature more than 1200 K is not recommended because it can decrease metallization degree.